Associate Professor Dr. Roslinazairimah produces electricity forecasting software for electric cars - Nur Hartini, Mohd Hatta (UMPSA, 2024)
PEKAN, 27 May 2024 – It is common knowledge that the use of electric cars in Malaysia is gaining attention, especially Malaysian automotive enthusiasts and consumers.